Effects of shear deformation and orthotropy on the buckling behaviour of oriented strand boards. Issue 6 (2nd November 2022) - Iwuoha, Stanley Emeka; Seim, Werner
ABSTRACT: The literature is replete with studies conducted on wood-based boards. However, studies involving the influence of orthotropy and shear deformation on the one-dimensional buckling behaviour of oriented strand boards are lacking. This study is a step-by-step approach towards investigating and discussing the influence of orthotropy and shear deformation on the bending and one-dimensional buckling behaviour of oriented strand boards using specimens which are 12, 18, and 25 mm in thickness, measuring 400 and 780 mm in length for the bending analyses and 400, 425, 450, 475, and 500 mm for the buckling analyses. FE-models were developed which considered the boards as orthotropic and were able to determine their load-displacement behaviour considering the effects of geometric non-linearities. Results of the analyses showed that orthotropy have significant effects on the bending while shear deformation influences both the bending and buckling behaviour of oriented strand boards. In bending, the effects are generally higher in the main strength than in the secondary strength direction. In buckling, it is a reduction in the buckling loads in a range of between 4% and 26%, compared to what would have been obtained using the Euler equation. An alternative Equation with a better ability to predict the one-dimensional buckling load of wood-based boards was presented and discussed.